Implementación de un sistema de geolocalización y aplicación móvil para las rutas turísticas del Cantón la Maná.”. - Villafuerte Toala, Karen Lisbeth (2020)
The Mana Canton receives a large number of foreign and national tourists, with an average of one thousand tourists of enthusiasts annually, currently has several tourist routes where people use a guide or maps to reach the different sites which are not efficient and this may cause people to not be able to easily access the different tourist sites, It can also be mentioned that in the maps are not updated therefore some tourist places are not registered what causes a problem to visit the tourist places. Mobile apps are designed to help identify tourist spots on maps displayed through the device’s GPS, the main idea is for a mobile device to detail the geographical location of the different tourist routes so that users can easily access from where they are where they will be able to look for the tourist destination, where the application indicates the distance from the point of origin to the point of destination of the tourist routes and the paths you can take to undertake the journey. Currently mobile applications and geolocation systems are the main axis of cities to promote tourism, where people can enter and choose the different natural tourist attractions of each town where you can see the point of departure and arrival to the chosen place. In this way, tourism is improved by leaving traditional media such as maps where some tourist sites are not fully identified causing confusion among tourists. For this reason, it is proposed the development and implementation of a geolocation system and mobile application for the tourist routes of La Mana Canton, with the intention of promoting tourism of the different towns that make up La Mana Canton, generating a great impact on tourists as they will have related information of the different places to visit and their experience will be efficient and satisfactory.